2023
DOI: 10.1007/s00134-023-07169-7
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of surgery associated acute kidney injury (EPIS-AKI): a prospective international observational multi-center clinical study

Abstract: Purpose The incidence, patient features, risk factors and outcomes of surgery-associated postoperative acute kidney injury (PO-AKI) across different countries and health care systems is unclear. Methods We conducted an international prospective, observational, multi-center study in 30 countries in patients undergoing major surgery (> 2-h duration and postoperative intensive care unit (ICU) or high dependency unit admission). The primary endpoint was the occurrence of PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 31 publications
3
11
0
1
Order By: Relevance
“…Our study found that the length and type of surgery, as well as intraoperative hemodynamics, vasopressors use, and blood transfusions were important predictors of postoperative AKI. In line with previous research 53 , we found that different types of surgery are associated with different incidence of postoperative AKI. Although the type of surgery is not modifiable, shortening the surgery time may reduce the risk of AKI for patients, especially high-risk patients 26 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study found that the length and type of surgery, as well as intraoperative hemodynamics, vasopressors use, and blood transfusions were important predictors of postoperative AKI. In line with previous research 53 , we found that different types of surgery are associated with different incidence of postoperative AKI. Although the type of surgery is not modifiable, shortening the surgery time may reduce the risk of AKI for patients, especially high-risk patients 26 .…”
Section: Discussionsupporting
confidence: 92%
“…We also found that use of vasopressors was associated with increased risk of AKI. This can be explained that use of vasopressors represents a surrogate marker for less stable hemodynamics 53 . Moreover, there are also data showing that higher vasopressor use affects renal function due to decreased renal perfusion 54 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the negative effects of FA on short and mid-term renal outcome are mainly present in patients with severe acute kidney injury (AKI 3) and were without relation to prior CKD status in our analysis. This goes in line with the recently published multicenter, observational EPIS-AKI study: patients developing a postsurgical AKI received intra- and postoperatively significantly more fluids compared to patients without AKI [ 41 ]. In addition, a postsurgical AKI was strongly associated with MAKE90, with the highest incidence in patients with AKI stage 3 [ 41 ].…”
Section: Discussionsupporting
confidence: 85%
“…The incidence of cardiac surgery-associated acute kidney injury (CS-AKI) may be as high as 50%, depending on the setting, patient cohort, and type of cardiac surgery [1,2]. Importantly, survival rates decrease with more severe AKI stages and even after complete recovery of CS-AKI, patients remain at an increased risk of persisting renal dysfunction or death [3].…”
Section: Cardiac-surgery Associated Acute Kidney Injurymentioning
confidence: 99%